Perlindungan Hak Keperdataan atas Tanah bagi Masyarakat Adat dalam Konflik Rempang Ditinjau dari Prinsip Negara Hukum - Assyahra Suci Oktaviani; Irmanjaya Thaher; Dyah Permata Budi Asri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The land conflict on Rempang Island, triggered by the national strategic project development of Rempang Eco-City, has sparked a sharp juridical debate between the aspects of state power (Machtsstaat) through investment policy instruments and the principles of the Rule of Law (Rechtsstaat) which emphasizes individual rights protection. This study aims to analyze the root causes of overlapping juridical claims between the Land Management Rights (HPL) held by BP Batam and the traditional physical land possession of the Rempang indigenous community based on the concept of the State's Right to Control (HMN), as well as to examine the legal standing and protection of uncertified land civil rights of the indigenous community viewed from the pillar of substantive justice in a Rule of Law. The research method applied is normative legal research utilizing a statute approach and a conceptual approach. The secondary data, consisting of primary, secondary and tertiary legal materials, were collected through literature review and analyzed qualitatively. The results indicate that the overlapping claims occurred due to the government's unilateral issuance of HPL over customary lands (tanah ulayat) that had been physically possessed peacefully, openly and generationally by the indigenous peoples (the Malay, Orang Laut and Orang Darat tribes) long before BP Batam or modern regulations were established. Within the perspective of substantive justice under the Rule of Law and the Basic Agrarian Law (UUPA), a land certificate is not the absolute source of rights but merely an administrative proof; thus, long-term physical possession in good faith (bezit/rechtsverwerking) by indigenous peoples constitutes a legally valid civil right that is constitutionally protected under Article 18B Paragraph (2) of the 1945 Constitution. Consequently, the civil legal protection for the Rempang indigenous community must be fulfilled through equal deliberation mechanisms (the right to consent or object to the project), fair compensation (covering both material and immaterial losses), or the granting of Communal Ownership Rights/land-sharing schemes to ensure that the indigenous people are treated as subjects of development rather than objects of land eviction for investor interests.